For the polynomial below, the -2 is a zero.

f(x)= x^3 - 2x^2 - 6x + 4

Express f(x) as a product of linear factors.

Use fractions or radicals in answers not decimals.

Thank you for the opportunity to help you with your question!

since -2 is a zero,so, x -(-2) =0 x +2 = 0therefore,f(x)= x^3 - 2x^2 - 6x + 4

= x^2(x+2) - 4x(x+2) +2(x+2)=(x^2 -4x+2)(x+2) (Answer)

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up